Effects of dietary supplementation with omega-3 fatty acid-rich linseed on the reproductive performance of ewes in subtropical climates - Akhtar, P.; Rajoriya, J. S.; Singh, A. K.; Ojha, B. K.; Jha, A. K.; Bisen, A.; Bajaj, Nitin K.; Ahirwar, M. K.; Raje, A.; Singh, A. P.; Peepar, S. S.; Mishra, A. K.; et al. (Frontiers in Veterinary Science, 2024)
The present study evaluated the effects of omega-3 (-3)fatty acid-rich linseed supplementations on the reproductive performance, endocrine, and biochemical profiles of ewes in a sub-tropical climate. Forty-eight acyclic and clinically healthy Marwari sheep, aged between 1.5-2.5 years with no parity, were divided into four groups: group I: ewes (n=12) were fed basal diet; group II: ewes (n=12) were fed basal diet along with 10% linseed; group III: ewes (n=12) were fed basal diets along with 15% linseed and group IV: ewes (n=12) were fed basal diets along with 20% linseed daily on dry matter basis. The experiment was done during the typical breeding season (October-November) of the sheep. The estrus induction rate was significantly (p<0.05) higher in all the treatments as compared to control. Estrus induction interval was significantly (p<0.05) less in group-III. The conception rate in group-I was significantly (p<0.05)lower. Control ewes also had a significantly (p<0.05) lower lambing rate than all the treatment groups. Serum progesterone concentrations differedsignificantly (p<0.05) between control and treatment groups on days 15, 30, 45, and 60. On treatment days 15 and 30, estrogen concentration was significantly (p<0.05) higher in all the treatments as compared to the group-I. In all the treatment groups, MUFA (Mono Unsaturated Fatty Acid) decreased significantly (p<0.05) whereas PUFA (Poly Unsaturated Fatty Acid) increased significantly (p<0.05) from day 15 onwards.In conclusion, 15% dietary linseed supplementation to ewes improved reproductive performance in subtropical climate. However, future studies are needed to further elucidate the role of linseed supplementation in sheep reproduction in sub-tropical climate.